The potential role of HPV oncoproteins in the PD-L1/PD-1 pathway in cervical cancer: new perspectives on cervical cancer immunotherapy - Li, Jin; Ma, Yuhong; Wu, Qixuemeng; Ping, Pengbin; Li, Juan; Xu, Xiaoying (Frontiers in Oncology, 2024)
Cervical cancer (CC) is a common malignant tumour of the female reproductive system that is highly harmful to women’s health. The efficacy of traditional surgery, radiotherapy and chemotherapy is limited, especially for recurrent and metastatic CC. With continuous progress in diagnostic and treatment technology, immunotherapy has become a new approach for treating CC and has become a new therapy for recurrent and metastatic CC. However, immunotherapy is not effective for all patients with CC. Therefore, factors related to immunotherapy efficacy in CC patients have become the focus of researchers. High-risk human papillomavirus (HPV) infection is an important factor that drives CC development and affects its progression and prognosis. Increasing attention has been given to the mechanism of the E5, E6 and E7 proteins, which are encoded by the HPV gene, in the occurrence and development of CC and their interaction with programmed cell death ligand-1/programmed cell death-1 (PD-L1/PD-1). Although some preliminary studies have been conducted on these topics, a comprehensive and systematic review of these topics is not available. This review comprehensively summarizes related articles from journals with impact factors greater than 3 and published in the past 5 years; it also reviews studies on the mechanism of HPV and CC, the mechanism of PD-L1/PD-1 axis regulation in CC, and the mechanism by which the interaction between HPV-related oncoproteins and the PD-L1/PD-1 pathway affects the development and prognosis of CC. This study provides theoretical support for the use of immunotherapies for CC, provides a basis for the selection of specific medications that target different HPV-related proteins, and provides a new perspective for the discovery of new immunotherapy targets for CC.